The Dangerous of Landuse Change at Semarang City - Hariyanto, Hariyanto (Forum Geografi, 2004)
Town in veri dynamic area. Growth of populatio, both natural andÂ  migration (urbanization), need area for the settlement and their activities. Neccesity of area for settlement canât be avoided. As a result, there is a landuse changing from non settlement area (set field, dry field, swamp, pond) to settlement area. This change will influence the hydro system balance in Semarang, for instance the extending of flooding area, etc. This research tries to find the characteristi of landuse change in Semarang. The characteristic involving how is pattern, process, intensity, and tendency. Pattern of landuse changing is sequence of using area before it became the settlement. Process of landuse change is by using the population are able to settle. Tendency is degree of landuse change speed. This research methods secondary analysis method, that is compare the statistic data of the landuse and map in 1980 and 2000. The sampling is by purposive random sampling method. Purposive is used so that all subdistricts in sub urban are represented. The sample area is the from percil in ertain coordinate. Result of this research shows that there is landuse changing rapidly that is decrease in the width of wet field, dry field, swamp, and pond. On the other hand, there is increase in width of settlement area and other dry land with intensity 232 ha every years. Wet field decrease 131,7 ha every years, swamp and pond 31 ha, and dry field 24,2 ha every years. In actually this landuse changing pattern is out of government policy. Semarang conversed. However, wet field is water habitat that is most potential. Tendency of sttlement growth is more facus on accesibility aspect and available cityâs facilities only. Number of settlement are built on land which not suitable, such labile land, or high slope. It proves that the government control function is weak. The conclusion from this research that landuse changing has to be ontrolled restrainded, so it will not cause the bad effet in Semarang. Width the wet field is 10% by width town, must be conservation. Because wet field has ecology value and economic value that is rice production and absorb labour in agricultural sector. Therefore, function role of government controll must be actived.